Fire behaviour of composite steel truss and concrete beam - Piloto, P.A.G. (2014)
This work compares the thermal behaviour on four different Composite Steel Truss and Concrete Beam (CSTCB), when submitted to two different fire conditions (one side and four sides of fire exposure). This analysis aims to be a preliminary assessment of a series of experimental tests. CSTCB with concrete plate delay temperature evolution on the steel truss and reinforcement, increasing fire resistance.